Favorable Conditions for Suspension Freezing in an Arctic Coastal Polynya. Issue 12 (8th December 2019) - Ito, Masato; Ohshima, Kay I.; Fukamachi, Yasushi; Hirano, Daisuke; Mahoney, Andrew R.; Jones, Joshua; Takatsuka, Toru; Eicken, Hajo
Abstract: Arctic sea ice incorporates and transports sediment, releasing it back into the water column during the melting season. This process constitutes an important aspect of marine sediment transport and biogeochemical cycling. Sediment incorporation into sea ice is considered to occur mainly through underwater interaction between frazil ice and resuspended sediment, referred to as suspension freezing. However, harsh environmental conditions have greatly limited field observations of this phenomenon. Analysis of mooring data from a coastal polynya in the northeastern Chukchi Sea, in conjunction with coastal ice radar and meteorological data, indicates that suspension freezing is a key mechanism for sediment entrainment into sea ice. During polynya episodes, acoustic backscatter data obtained by an Acoustic Doppler Current Profiler showed the presence of frazil ice from the surface down to 20‐ to 25‐m depth, coinciding with in situ and potential supercooling. Underwater frazil ice persisted over 1 week under windy, turbulent water column conditions. A combination of the turbidity and Acoustic Doppler Current Profiler backscatter data revealed upward sediment dispersion associated with strong currents during the polynya episodes. The fact that frazil ice and resuspended sediment were detected at the same depth and time strongly suggests the interaction between ice crystals and sediment particles, that is, suspension freezing. Plain Language Summary: Sea ice incorporates, transports, and releases particulate matter. These processes constitute an important aspect of the biology, biogeochemical cycling, and pollutant transport in polar oceans. Seafloor sediments serve as the most important source of such particulate matter; however, the process of sediment incorporation into sea ice remains poorly explored. We conducted a year‐long study of sediment resuspension and entrainment processes, using underwater sensors deployed in the Chukchi Sea. During winter, wind‐driven offshore transport of sea ice created area of open water and newly grown thin ice that persisted for several days, so‐called coastal polynya or flaw lead system. Our sensors recorded small ice crystals, so‐called frazil ice, that formed in the water column when water temperatures were below freezing point (supercooling). During some of these episodes, sediment was resuspended from the seafloor and dispersed upward by the strong currents, bringing it into water depths at which frazil ice was encountered. Such conditions provide for opportunities that allow frazil ice crystals or aggregates to capture resuspended sediment, a process referred to as suspension freezing. Based on this study, we propose that suspension freezing commonly occurs in shallow Arctic polynyas, serving as a key process of sediment incorporation into sea ice. Key Points: ADCP data provided evidence of frazil ice penetrating to ~25 m in the water column during supercooling episodes in a coastal polynya The combination of acoustic and optical measurements revealed underwater frazil ice‐sediment interaction at water depths of 10–25 m Suspension freezing can often occur in shallow polynyas and is suggested to be the dominant process of sediment incorporation into sea ice